The Impact of Urbanization and Industrialization on River Water Quality: A Case Study of Sungai Kluang, Bayan Lepas, Pulau Pinang - Ibrahim, Ab. Latif (Universiti Sains Malaysia, 2002)

(untitled)
Increasing population, rapid urbanization and rapidly intensifying human activities have exerted immense pressure on water quality. Whenever human and industrial wastes are not properly managed, surface waters as well as ground waters become the sink for receiving such wastes. When effluents from industries are discharged into river channels, the river water will be polluted physically, biologically and chemically. This is due to the increased concentration of dissolved solids, toxic chemical, BOD loadings, heavy metals and other pollutants. Pesticides and weedicides from agricultural areas add to the increasingly polluted water sources.